Filozofia przyrody w alchemii. Zarys związków - Radosław Kazibut (Studia Philosophiae Christianae, 2020)
The aim of my discussion is to present the relationship between the research of natural philosophers and the development of the alchemical tradition. I refer to specific concepts formulated in the history of alchemy to argue that research in this field took the form of complex systems delineating coherent pictures of the natural world and, therefore, that alchemy presupposes certain types of natural philosophy.